Sirtuin Oxidative Post-translational Modifications - Kalous, Kelsey S.; Wynia-Smith, Sarah L.; Smith, Brian C. (Frontiers in Physiology, 2021)
Increased sirtuin deacylase activity is correlated with increased lifespan and healthspan in eukaryotes. Conversely, decreased sirtuin deacylase activity is correlated with increased susceptibility to aging-related diseases. However, the mechanisms leading to decreased sirtuin activity during aging are poorly understood. Recent work has shown that oxidative post-translational modification by reactive oxygen (ROS) or nitrogen (RNS) species results in inhibition of sirtuin deacylase activity through cysteine nitrosation, glutathionylation, sulfenylation, and sulfhydration as well as tyrosine nitration. The prevalence of ROS/RNS (e.g. nitric oxide, S-nitrosoglutathione, hydrogen peroxide, oxidized glutathione, and peroxynitrite) is increased during inflammation and as a result of electron transport chain dysfunction. With age, cellular production of ROS/RNS increases; thus, cellular oxidants may serve as a causal link between loss of sirtuin activity and aging-related disease development. Therefore, the prevention of inhibitory oxidative modification may represent a novel means to increase sirtuin activity during aging. In this review, we explore the role of cellular oxidants in inhibiting individual sirtuin human isoform deacylase activity and clarify the relevance of ROS/RNS as regulatory molecules of sirtuin deacylase activity in the context of health and disease.